Expression of human proacrosin in Escherichia coli and binding to zona pellucida - Furlong, Laura Ines (2000)
Proacrosin is a multifunctional protein present in the sperm acrosome. This study characterizes the expression of human proacrosin in bacteria and assesses zona pellucida binding activity. The cDNA encoding human proacrosin was subcloned in pGEX-3X and pET-22b vectors. In the pGEX system, expression of the full-length fusion protein was not detected. In the pET system, an expression product with an apparent molecular size similar to that expected for the proenzyme (Rec-40, 42-44 kDa) was recognized by a monoclonal antibody to human acrosin, AcrC5F10. A 32-34-kDa protein (Rec-30), not recognized by AcrC5F10 on Western blots, was the major expression product. Proteins of 21 (Rec-20) and 18 (Rec-10) kDa were recovered as insoluble expression products as were Rec-40 and Rec-30, and truncated products from the C terminus were detected in the soluble fraction. Rec-40 and Rec-30 coexisted at any culture time tested. Immune serum raised against Rec-30 (AntiRec-30) stained the acrosomal region of permeabilized human spermatozoa and recognized the recombinant proteins and proacrosin from human sperm extracts. Amino acid sequence analysis indicated that Rec-30, Rec-20, and Rec-10 are N-terminal fragments of proacrosin. The recombinant proteins Rec-40, -30, -20, and -10 were found to interact with homologous (125)I-zona pellucida glycoproteins.